STRATEGI EMPLOYEE RELATIONS DALAM MENINGKATKAN PELAYANAN EXCELLENT PADA PELAYANAN BANDAR UDARA INTERNASIONAL SOEKARNO - HATTA TERMINAL 3U - Rully Rahmat; Henni Gusfa (Universitas Mercu Buana, 2019)
This study aims to determine the role of employee relations strategy in improving excellent service at the service of Soekarno-Hatta International Airport-Terminal 3. As the foundation of this study, researchers use employee relationship concept by Van Riel. Ability to manage internal communication within and between groups within the organization by handling structures systematically, flow, content, and climate in order to improve the implementation of the organization's own strategic goals. This research uses post-positivistic paradigm with case study method. Data collection was done with in-depth interviews. Based on the results of research and data analysis has been done then obtained the conclusion that the relationship of good employees can be seen from the way they interact and establish communication rope by holding Gathering program to improve the excellent service. With the doing of employee relations activities in PT. Angkasa Pura II such as Contact Center World (CCW) program and Indonesia Contact Center Association (ICCA) and accompanied by sincere internal communication with SOP, it can improve the excellent service. Keywords: Strategy, Employee Relations, Excellence Service